“Al-Arabiyyah Sahlah” Sebagai Label Perspektif Baru Dalam Menyongsong Pembelajaran Bahasa Arab Di Era New Normal - Ayu Nur Islami (Jurnal DinamikA, 2020)
This research was conducted by disseminating questionnaires and concluded that 23 out of 36 people assumed Arabic was difficult. This is what is behind the writing of this article. Kalam Allah and Rasulullah Arabic-speaking Apostles have been absolutely a guide to life, so muslims should try to learn it. If psychologically only Arabic is considered difficult, then it will be a inhibition of concern for many people to learn it. The purpose of this article was to renew the sensitivity of Arabic which could later become the main capital to mobilize interest and motivation for learners. In addition, methodological renewal is no less important, where the techniques and teaching methods of educators must be completely improved. Senior educators, students, even arabic language institutions must equip themselves with the right teaching competencies. Even this new normal era becomes both an opportunity and a challenge to fix it all. So there needs to be a deeper discussion to make it easier for the Al-Arabiyyah Sahlah (Arabic to be easy) to learn, as the Divine Kalam promises "And indeed, we have made it easy for the Qur'an to be warned, so will anyone take a lesson?"Keyword : Al-Arabiyyah Sahlah, Perspective,  Learning.